The N-terminal region located upstream of the TCP domain is responsible for the antagonistic action of the Arabidopsis thaliana TCP8 and TCP23 transcription factors on flowering time. (March 2023) - Camoirano, Alejandra; Alem, Antonela L.; Gonzalez, Daniel H.; Viola, Ivana L.
Abstract: TCP proteins (TCPs) are plant-exclusive transcription factors that exert effects on multiple aspects of plant development, from germination to flower and fruit formation. TCPs are divided into two main classes, I and II. In this study, we found that the Arabidopsis thaliana class I TCP transcription factor TCP8 is a positive regulator of flowering time. TCP8 mutation and constitutive expression delayed and accelerated flowering, respectively. Accordingly, TCP8 mutant plants showed a delay in the maximum expression of FT and reduced SOC1 transcript levels, while plants overexpressing TCP8 presented increased transcript levels of both genes. Notably, the related class I protein TCP23 showed the opposite behavior, since TCP23 mutation and overexpression accelerated and retarded flowering, respectively. To elucidate the molecular basis of these differences, we analyzed TCP8 and TCP23 comparatively. We found that both proteins are able to physically interact and bind class I TCP motifs, but only TCP8 shows transcriptional activation activity when expressed in plants, which is negatively affected by TCP23. From the analysis of plants expressing different chimeras between the TCPs, we found that the N-terminal region located upstream of the TCP domain is responsible for the opposite effect that TCP8 and TCP23 exert over flowering time and regulation of FT and SOC1 expression. These results suggest that structural features outside the TCP domain modulate the specificity of action of class I TCPs. Highlights: The Arabidopsis class I TCP TCP8 acts as positive regulator of flowering time. TCP8 and the related class I TCP TCP23 antagonistically regulate flowering time and FT and SOC1 expression. Both TCP8 and TCP23 specifically bind class I TCP target sequences in vivo and form heterodimers. TCP8 activates transcription and its transcriptional activity is affected in the presence of TCP23. The N-terminal portions upstream of the TCP domain determine the differential effects of TCP8 and TCP23 on flowering time.